21 Impact of Breed and Method of Semen Collection on Viability and Membrane Integrity of Goat Spermatozoa. (8th March 2022) - Reese, Tiffany-Briana; Kouakou, Brou; Singh, Mahipal; Schauston, Miller; Moawad, Adel
Abstract: Goats have potential to be genetically improved for meat and milk. Artificial insemination is an important technique used to enhance genetic gain through dissemination of selected male traits. One reason for huge variability in fertility rates in goats is the semen quality, which is affected by breed, collection method, and freezing procedures. Here we investigated effect of breeds (Saanen versus Alpine) and semen collection methods (artificial vagina; AV versus electroejaculation; EE) on the quality of goat spermatozoa. Semen collected from Saanen and Alpine bucks by either AV or EE was evaluated for its color, consistency, and volume. Besides, sperm motility, concentrations, viability, abnormalities, and membrane integrity were assessed. At least three ejaculates were collected from each breed and data were analyzed by student t-test. Results showed that colors of samples collected from the two breeds were white to yellow and the consistency ranged from watery to creamy. Irrespective to the collection method, average volume of ejaculates was higher for Alpine than Saanen (1350 vs. 880 µl for AV and 1066 vs. 987.5 µl for EE). Sperm motility and concentrations were higher (P ≤ 0.05) in Alpine than Saanen semen for both methods. Within the same breed, these parameters were higher (P ≤ 0.05) for AV than EE. Percentage of viable spermatozoa was higher for Alpine than Saanen bucks (80.0% vs. 64.5% in AV) and (52.42% vs. 41.35% in EE). However, sperm abnormalities were lower (P ≤ 0.05) in Alpine semen. Sperm membrane integrity tended to be higher in Alpine semen. In conclusion, semen collected from Alpine bucks had higher quality than those obtained from Saanen ones. Furthermore, collection of semen by AV improved sperm motility and viability than EE in both breeds. These findings suggest that both breeds and method of semen collection could influence the viability and fertility of goat sperm.